2018
DOI: 10.1063/1.5016054
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics study of the Eley-Rideal reaction of H + Cl–Au(111) → HCl + Au(111): Impact of energy dissipation to surface phonons and electron-hole pairs

Abstract: The reaction between an impinging H atom and a Cl atom adsorbed on Au(111), which is a prototype for the Eley-Rideal mechanism, is investigated using ab initio molecular dynamics at different incidence angles. The reaction yielding gaseous HCl with large internal excitation proceeds via both direct and hot-atom mechanisms. Significant energy exchange with both surface phonons and electron-hole pairs has been observed. However, their impact on the reactivity and final state distributions was found to be limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…74,114,582 Another topic addressed with DFMDEF is Eley-Rideal reactions, of H-atoms on Cu(111), 583 of D-atoms with CD 3 pre-adsorbed to Cu(111), 584 and of H with Cl preadsorbed to Au (111). 585 Finally, DFMDED calculations investigated scattering of N-atoms from Ag(111), 74,541,582 and dynamic displacement of CO pre-adsorbed to Cu (111) by incident H-atoms. 586 The DFMDEF calculations on vibrational excitation of H 2 on Cu (111) showed that the GLO + LDAF friction method is remarkably accurate in its description of vibrational excitation, at least within the limits of quasi-classical dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…74,114,582 Another topic addressed with DFMDEF is Eley-Rideal reactions, of H-atoms on Cu(111), 583 of D-atoms with CD 3 pre-adsorbed to Cu(111), 584 and of H with Cl preadsorbed to Au (111). 585 Finally, DFMDED calculations investigated scattering of N-atoms from Ag(111), 74,541,582 and dynamic displacement of CO pre-adsorbed to Cu (111) by incident H-atoms. 586 The DFMDEF calculations on vibrational excitation of H 2 on Cu (111) showed that the GLO + LDAF friction method is remarkably accurate in its description of vibrational excitation, at least within the limits of quasi-classical dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…However, the validity of LDFA-IAA has been continuously questioned due to the lack of intrinsic anisotropy in the friction tensor 15,3741. The latter issue has been partially addressed via the Hirshfeld partitioning of the overall system density to contributions of relevant atoms, which has recently been applied to the relaxation of hot atoms and molecules on metal surfaces 27,38,42…”
Section: Introductionmentioning
confidence: 99%
“…Within this local density friction approximation (LDFA), 31 the atomic friction coefficient can be obtained from the scattering properties of the Kohn-Sham (KS) wave functions in a static density functional theory (DFT) calculation. 30 Given its simplicity and efficiency, combined with high-dimensional DFT-based PESs or on-the-fly electronic structure calculations, the LDFA-based MDEF model has enabled a firstprinciples description of the non-adiabatic energy loss in various processes of atoms/molecules interacting with metal surfaces, 9,[32][33][34][35][36][37][38][39][40][41] sometimes yielding close to quantitative agreement with experiments. 18,[42][43] Despite these successes, LDFA has been continuously questioned in describing non-adiabatic interactions between molecules and metal surfaces, because the atomic friction coefficients intrinsically lack the directional dependence and molecular anisotropy that arises from the electron-nuclear coupling of a many-electron system described in a realistic potential.…”
Section: Introductionmentioning
confidence: 99%